KOMUNIKASI INTERPERSONAL GURU DAN MINAT BELAJAR SISWA - Aziz, Jamil Abdul (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2019)
The purpose of education will not be realized without the presence of successful educators in the ongoing education process. One important teacher skill means communication skills. This is the reason for the researchers about MTs Muhammadiyah 1 Ciputat. In this study, researchers used a correlational analysis method, by studying quantitative. Data collection tools include: interviews, observation, documentation and questionnaires. This questionnaire distribution technique uses random sampling techniques. When processing the data after the data from the questionnaire was obtained, the researcher used the moment r 'formula as the product. The results showed there was an interaction or positive between teacher and student interpersonal communication (Variable X) with student interest in learning (Variable Y) in the subjects of Islamic Cultural History.